2017
DOI: 10.1016/j.molp.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Complexities between Auxin, Cytokinin, and Ethylene in Arabidopsis Root Development: From Experiments to Systems Modeling, and Back Again

Abstract: Understanding how hormones and genes interact to coordinate plant growth in a changing environment is a major challenge in plant developmental biology. Auxin, cytokinin, and ethylene are three important hormones that regulate many aspects of plant development. This review critically evaluates the crosstalk between the three hormones in Arabidopsis root development. We integrate a variety of experimental data into a crosstalk network, which reveals multiple layers of complexity in auxin, cytokinin, and ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
125
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 100 publications
(198 reference statements)
1
125
0
2
Order By: Relevance
“…There is a complex crosstalk between ethylene and other plant hormones at the level of signaling and/or biosynthesis, the latter of which includes both transcriptional and posttranscriptional regulation of ACS (reviewed in Kazan and Manners, 2012;Muday et al, 2012;Van de Poel et al, 2015;Shigenaga and Argueso, 2016;Hu et al, 2017;Liu et al, 2017;Zemlyanskaya et al, 2018;Bürger and Chory, 2019;Qin et al, 2019). For example, cytokinin and brassinosteroid additively increase the stability of type-2 ACS proteins independently of their TOE domains ).…”
mentioning
confidence: 99%
“…There is a complex crosstalk between ethylene and other plant hormones at the level of signaling and/or biosynthesis, the latter of which includes both transcriptional and posttranscriptional regulation of ACS (reviewed in Kazan and Manners, 2012;Muday et al, 2012;Van de Poel et al, 2015;Shigenaga and Argueso, 2016;Hu et al, 2017;Liu et al, 2017;Zemlyanskaya et al, 2018;Bürger and Chory, 2019;Qin et al, 2019). For example, cytokinin and brassinosteroid additively increase the stability of type-2 ACS proteins independently of their TOE domains ).…”
mentioning
confidence: 99%
“…As JAZs and MYC2 are key factors in plant growth and development as positive and negative regulators, respectively, they may mediate JA-dependent growth inhibition under stress conditions [12][13][14].Plant hormones have their own specific biosynthetic and signaling pathways, but their roles in plant development and physiology overlap. This suggests that plant hormones modulate plant growth and physiology through interactions with other hormones, and the extensive interplay between auxin and cytokinin in the regulation of all aspects of plant growth and development supports this idea [15,16]. JA mediates the plant response to biotic and abiotic stresses through interaction with salicylic acid, ethylene, and abscisic acid (ABA), and details of this crosstalk and its underlying molecular mechanisms have been well reported in previous studies [3,[17][18][19].…”
mentioning
confidence: 59%
“…4a,c). Previous protein-protein interaction analyses revealed that ETR1 interacts with key components of the cytokinin signaling pathway, including the Arabidopsis histidine-containing phosphotransfer proteins (AHPs) and response regulators (ARRs) (Urao et al, 2000;Dortay et al, 2008;Scharein et al, 2008;Liu et al, 2017). ETR1 has a functional his kinase (Gamble et al, 1998;Moussatche & Klee, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To further test this possibility, we quantified the expression of two type-A ARRs (ARR5 and ARR7), in etr1-6 and Col-0 plants under both infected and noninfected conditions. These ARRs were selected because they have been shown previously to change expression in the syncytium formed by H. schachtii in Arabidopsis (Szakasits et al, 2009;Siddique et al, 2015), in addition to their potential role in mediating the crosstalk between ethylene and cytokinin signaling (Liu et al, 2017). Under noninfected conditions, the expression of ARR5 and ARR7 was downregulated in etr1-6 compared to Col-0 plants (Fig.…”
Section: Etr1 May Function Autonomously Of the Canonical Ethylene Sigmentioning
confidence: 99%